Valuation Of Eq-5d-5l Study For The Malaysian Population - Thakumar, Annushiah Vasan (2020)
With the rise of healthcare expenditure, prudent resource allocation decisions become vital and economic evaluations offer valuable information in guiding these decisions. Cost-utility analysis is one such alternative with outcomes measured using quality-adjusted life years (QALYs). QALYs takes into consideration health preference weights, with generic preference-based measures (PBMs) being most commonly used to generate these weights. One of the most widely used instrument todate, EQ-5D-5L has informed economic evaluation decisions throughout the world. However, Malaysia has yet to validate the measure and apply it to generate a countryspecific value set. Therefore, the main objective of this thesis is to estimate a valid EQ- 5D-5L value set for Malaysians. Two focus group discussions (FGDs) were held to explore the EQ-5D-5L dimensions understanding in Malaysians and investigate potential dimensions (bolt-ons) that may complement the concept of health. Next, using 100 conveniently sampled respondents, the influence of these identified bolt-ons on the current EQ-5D-5L dimensions were tested in a pilot setting in Penang. Subsequently, employing a cross-sectional multi-stage sampling design, an EQ-5D-5L nationwide valuation study was carried out by 18 trained interviewers on 1137 Malaysian general population. The psychometric properties of EQ-5D-5L were also assessed in the process. A variety of modelling methods were fitted onto the valuation data and performance of these models in predicting health state values were assessed using robust techniques. Another value set was estimated, but applying an earlier version of the instrument, EQ-5D-3L.